Analisis Implementasi P5 Dimensi Kebhinekaan Global dalam Mengembangkan Pendidikan Karakter Cinta Tanah Air Peserta Didik Kelas IV di SD Negeri Jirapan 3 Sragen - Lina Rahmatika; Oktiana Handini; Ani Restuningsih (International Forum of Researchers and Lecturers, 2025)
This study aims to identify various inhibiting factors and the steps that have been taken, as well as to analyze the implementation of P5 dimensions of global diversity in developing character education for love of country for grade IV students at SD Negeri Jirapan 3 Sragen. This study was conducted at SD Negeri Jirapan 3 Sragen using a qualitative descriptive approach. The data used consisted of primary and secondary data, obtained through observation, interviews, and documentation conducted by the researcher together with the principal, teachers, and grade IV students. The subjects in this study included the principal, teachers, and grade IV students, with a sample size of three people. Data collection techniques were carried out through direct observation, in-depth interviews, and documentation as supporting data. To ensure the validity of the data, the researcher implemented strategies such as increasing perseverance in the research process, triangulation of techniques and data sources, and utilization of reference materials. The data analysis process was carried out through several stages, namely data collection, data reduction, data presentation, and drawing conclusions and verification. According to the findings of the analysis that the researcher has conducted, it shows that SD Negeri Jirapan 3 Sragen has implemented P5 dimensions of global diversity in developing character education of love for the homeland of grade IV students well. This is reflected through learning, self-development in students, and habituation activities at school such as religious activities, scouts, extracurricular karawitan, and school activities in commemorating national holidays, as well as projects for making handicrafts and regional specialties that have been running well. The existing inhibiting factors have been successfully overcome through various efforts that have been carried out well.